An anionic iridium(iii) complex as a visible-light absorbing photosensitizer. Issue 32 (20th July 2018) - Takizawa, Shin-ya; Kano, Ryoto; Ikuta, Naoya; Murata, Shigeru
Abstract : A new anionic Ir(iii ) photosensitizer bearing coumarin dyes has been developed and applied to the visible-light-driven hydrogen generation. Abstract : In this work, a new anionic Ir(iii ) complex (Ir2 ) was synthesized using coumarin 6 and orotate ligands, and its use as a photosensitizer in photochemical hydrogen (H2 ) generation was demonstrated. For comparison purposes, we also prepared a known anionic Ir(iii ) complex (Ir1 ) bearing 2-phenylpyridine and orotate ligands, which was previously reported as an emitting material by another research group. The photophysical properties of complexesIr1 andIr2 were examined in several solvents including aqueous acetonitrile (CH3 CN–H2 O), which is frequently used in photocatalytic H2 -generating experiments.Ir1 was found to be weakly emissive in CH3 CN–H2 O, which is probably due to the effect of hydrogen bonding between the orotate ligands and H2 O molecules. In sharp contrast, Ir2 exhibited remarkable properties that include strong visible-light absorption ( ε = 78 800 M −1 cm −1 at 462 nm), a high phosphorescence quantum yield (50%), and a long-lived excited state (15 μs), even in the same solvent. Actually, Ir2 functioned as a photosensitizer during visible-light-driven H2 generation using sodium ascorbate and a cobalt(iii ) diglyoxime complex as the electron donor and water-reduction catalyst, respectively. To the best of our knowledge, this is the first example of the use of an anionic Ir(iii ) sensitizer in a photoinduced electron-transfer reaction. The results of this study suggest thatIr2 can be applied to future photochemical H2 -generating systems that are based on ion-paired photocatalysts.